Catalytic Cracking of Used Cooking Oil Using Cobalt-impregnated Carbon Catalysts - Prabasari, Ira Galih; Sarip, Rozie; Rahmayani, Suci; Nazarudin, (Makara Journal of Science, 2019)
This study investigated the cracking of used cooking oil using cobalt-impregnated carbon catalysts (Co-carbon) to produce biofuel. Carbon was impregnated with cobalt at concentrations of 1%, 2%, and 3% to produce Co-carbon catalysts. X-ray diffraction and scanning electron microscopy (SEM) demonstrated the amorphous nature of the catalysts. SEM-energy-dispersive X-ray analysis confirmed the successful impregnation of cobalt into carbon at levels of 4.46%, 6.74%, and 0.86% and further revealed that the Co-carbon catalysts contained pores and that each of them was slightly unique. The cracking procedure was conducted at 450 °C, 500 °C, and 550 °C. Analysis of the catalytic cracking products revealed that the highest liquid oil fraction was obtained by catalytic cracking at 500°C using 1% Co-carbon catalyst, which also provided the lowest activation energy (Ea). Catalytic cracking using 3% Co-carbon provided the highest yield of diesel oil (C12–C18) in the product.